Embolo/sclerotherapy for the treatment of hand arteriovenous malformations: a single-center retrospective cohort experience - Fan, Xueqiang; Zhang, Jianbin; Liu, Peng; Ye, Zhidong (Frontiers in Surgery, 2023)
Purpose: To retrospectively report our preliminary experience of treating hand arteriovenous malformations (AVMs) with embolo/sclerotherapy. Materials and methods: Retrospectively review the medical record of 13 consecutive patients with hand AVMs from January 2018 to December 2021. The demographics, treatment detail, outcomes data and complications were reviewed and reported. Results: According to the angiographic findings and Yakes classification criteria, type II present in 4 lesions, type IIIa in 6 lesions and type IIIb in 3 lesions. The mean stretched length of coils for 1 treatment episode was 95 cm. The mean absolute ethanol dosage was 6.8 mL (range 4-30mL), 3% polidocanol foam dosage was 10 mL for every patient. Interstitial sclerotherapy with 150,000 IU bleomycin is carried out for every patient. The post-operative arterial-dominant outflow vein pressure index (AVI) increased in the 29 procedures (6.55±1.68 vs. 9.38±2.80, P < 0.05). The Mann-Whitney U test showed that the post-operative AVI was higher in patients without re-intervention (P < 0.05). Conclusion: Embolo/sclerotherapy can be effective and safe for hand arteriovenous malformation. The arterial-dominant outflow vein pressure index increased significantly after embolo/sclerotherapy, and the index maybe valuable in predicting recurrence in further study.